Strategy to Select and Grade Efficient Dyes for Enhanced Photo-Absorption - A. Babangida; J. B. Yerima; A. D. Ahmed; S. C. Ezike (African Scientific Reports, 2022)
In this paper, a simple strategy to select and grade efficient natural dye-sensitizers for photo-absorption is developed. The selection criteria help to choose efficient dye for construction of solar cell. On the other hand, the dye-grade technique based on light and matter interaction parameters (absorbance, anthocyanin, and light harvesting efficiency) further reduce the number of dyes for efficient dye-sensitized solar cell (DSSC) production. The result shows that the dyes extracted from witch seed flower (Striga hermonthica), flamboyant flower (Delonix regia), and bitter gourd (Momordica charantia) have dye-grade 1, are the most efficient photo-absorber for enhanced DSSC fabrication while guava peel dye has grade 10 being the least efficient dye. The selection criteria and dye-grade techniques provide surer way of getting promising dyes for effiective DSSC production than choosing the dyes randomly based on some features like their colors and abundance.